Quality Analysis of Academic Services: Case study of Industrial and Systems Engineering Campus Caborca, University of Sonora, Mexico - Vega-Robles, Arturo (2015)
Educational institutions that wish to compete in this globalized world, the need to set standards in quality of services they offer, as their products or processes are not tangible and the quality of them depends on the perception of customers. The objective of this study is to determine the level of quality in academic services in Industrial and Systems Engineering Campus of the University of Caborca Sonora. To obtain feedback from users, the SERVQUALing instrument was used, and by a four-dimensional analysis of factors that explain 62.02% of the total variance of the data is identified. For this study, the level of service is 81.24%, considered very good, requiring analysis necessary to establish an improvement plan.